MODELLING THE FLEXIBLE SCHEDULES OF WORK OF INDUSTRIAL ENTERPRISES MANAGERS - Evgen Didenko (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of the article is analyzing ways of using the potential capabilities of managers of industrial enterprises to implement high-performance activities as a factor of direct influence on the state and nature of the relationship between an employer and an employee. The goal is to build a model for flexible scheduling the work of enterprise managers that take into account the priority of solving production tasks in the subsystem of the personnel management of the decision support system for organizing the activities of an industrial enterprise. The objectives are to develop an economic and mathematical model that enables taking into account the rhythm of the fluctuations of the opportunities for achieving high results in the managerial activity and the activation of hidden potentials of managers by introducing flexible forms of managers’ work into the scheduled plans of the production activities of industrial enterprises. The general scientific methods such as system analysis, structural analysis and specific network methods are used. The following results are obtained. The conceptual model of activating the efficiency of managers’ production activities is suggested; the manager’s activities are activated by minimizing the involvement of managers in performing production tasks when the values of the indicators of managers’ potential capabilities are low, which objectively reduces the productivity of managerial work. At the same time, it is suggested to use the manager’s capabilities at a time that coincides with the opportunities for high-performance work by adapting flexible schedules of managers’ work to the requirements of the scheduled plans of an industrial enterprise. The integral indicator for assessing the impact of the rhythms of managers’ activities on the state of their labour productivity is suggested for using in the models of organizing the activity of industrial enterprises. Recommendations are given to minimize the risks of disregarding the terms of employment contracts that are caused by the potential inability to obtain high indicators of managers’ labour activities and to explain the advantages of using flexible schedules of managers’ work to the representatives of an employer’s personnel services. Conclusions. Modelling of flexible schedules of the work of managers of industrial enterprises enables correcting the work of managers at an enterprise taking into account the wave character of managers’ readiness for highly productive work according to the positive feedback principle. The recommendations for calculating the integral indicator of assessing the impact of the rhythms of managers’ activities on the state of productivity of their work are given. The obtained results can be used to determine more specifically the obligations of employers and managers as the parties of labour relations to agree on the duration, regularity, and the rhythm of managers’ performance of their work-related obligations.